2020
DOI: 10.1002/pat.4945
|View full text |Cite
|
Sign up to set email alerts
|

Study of thermomechanical properties of hybrid tire cord

Abstract: Thermomechanical properties of tire cords, which have a considerable influence on tire functions, were investigated in the current research. The nylon and polyester cords are the most commonly used polymers in the tire. Many efforts have been made to produce a new tire cord having the capability of integrating the desired properties of these two polymers into one cord. In this study, a new cord structure was developed using nylon 6,6 and polyester tire yarns. The effect of thermal treatment was studied at the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…110 The renewable lyocell fibers partially replace the aromatic polyamide fibers, thus reducing the dependence of the curtain fabric on the use of petrochemical resources. Mahdavipou and others studied the thermodynamic properties of PA66/PET hybrid curtain fabrics, 111 and their experimental results showed that the residual shrinkage rate and shrinkage force will increase with increasing load at any heat treatment temperature. To date, PET/nylon hybrid curtain fabrics, aromatic polyamide/nylon or polyester hybrid curtain fabrics, and other fabrics have been studied and applied as skeleton materials for the crown belts of radial tires.…”
Section: Hybrid Curtain Fabricmentioning
confidence: 99%
“…110 The renewable lyocell fibers partially replace the aromatic polyamide fibers, thus reducing the dependence of the curtain fabric on the use of petrochemical resources. Mahdavipou and others studied the thermodynamic properties of PA66/PET hybrid curtain fabrics, 111 and their experimental results showed that the residual shrinkage rate and shrinkage force will increase with increasing load at any heat treatment temperature. To date, PET/nylon hybrid curtain fabrics, aromatic polyamide/nylon or polyester hybrid curtain fabrics, and other fabrics have been studied and applied as skeleton materials for the crown belts of radial tires.…”
Section: Hybrid Curtain Fabricmentioning
confidence: 99%